2022
DOI: 10.1186/s12966-022-01321-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal change in physical activity and adiposity in the transition from adolescence to early adulthood: the 1993 Pelotas cohort study

Abstract: Background In the current Physical Activity Guidelines (PAG) for moderate- and vigorous-intensity physical activity (MVPA), abrupt transition from ≥ 60 min/day [youth PAG] to ≥ 150 min/week (≥ 22 min/day on average) [adult PAG] during emerging adulthood is poorly justified. The aim of this study was to examine body fat mass changes according to whether meeting the youth and adult PAGs in late adolescence (age 18 years) to early adulthood (age 22 years). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…As a result, there is a dearth of data on the mental (quality of life and learning experience) and physical (physical self-esteem) outcomes associated with different PA levels among young adults and college students. There is a special interest in the college population because of the unique challenges that this cohort of young adults faces as they make the transition from high school to college [ 36 , 37 ], encountering greater accountability, competition, academic pressure, and time management demands [ 38 , 39 , 40 ]. Decreased physical activity (PA), expanded emotional and psychological stress, and sleep problems are all possible side effects of this change [ 30 , 36 ], as well as the onset of risky health behaviors such as drug and alcohol abuse [ 41 ], which may have an adverse effect on learning experience and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there is a dearth of data on the mental (quality of life and learning experience) and physical (physical self-esteem) outcomes associated with different PA levels among young adults and college students. There is a special interest in the college population because of the unique challenges that this cohort of young adults faces as they make the transition from high school to college [ 36 , 37 ], encountering greater accountability, competition, academic pressure, and time management demands [ 38 , 39 , 40 ]. Decreased physical activity (PA), expanded emotional and psychological stress, and sleep problems are all possible side effects of this change [ 30 , 36 ], as well as the onset of risky health behaviors such as drug and alcohol abuse [ 41 ], which may have an adverse effect on learning experience and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Using an independent t-test sample method, the mean of the early and late responses was determined. Non-response bias was not an issue in our study because no statistically significant differences were observed [54].…”
Section: Stage One: Results Of Descriptive Analysismentioning
confidence: 72%
“…The values for the mean ranged anywhere between 2.22 and 3.15, while the values for the standard deviation were between 0.876 and 1.05. As a direct result, the data were found to be more dispersed and less concentrated in the center [54]. Additionally, the virtual observation of the skewness and kurtosis scores (data distribution) indicated no values that surpassed −2 or +2, giving evidence of normal normality distribution (univariate) [55].…”
Section: Stage One: Results Of Descriptive Analysismentioning
confidence: 88%
“…PA levels were assessed and recorded using Actigraph GT3X+ accelerometers (ActiGraphTM, Pensacola, FL, USA) and Actilife software (version 6.13.4), which are valid and reliable tools for recording and measuring PA levels in adolescents [ 66 , 67 ].…”
Section: Methodsmentioning
confidence: 99%